2012
DOI: 10.1007/s13181-012-0216-4
|View full text |Cite
|
Sign up to set email alerts
|

A Trial Investigating the Symptoms Related to Pine Nut Syndrome

Abstract: During the last few years, thousands of cases of pine nut-related dysgeusia have been reported. The symptoms involved are predominantly related to taste disturbances such as a constant bitter or metallic taste. The taste disturbance has been reported to occur 1-2 days after ingestion of pine nuts from the species of Pinus armandii. This paper describes a small trial where six volunteers consumed six to eight pine nuts suspected to cause dysgeusia. Incubation periods, symptoms and their duration were recorded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Since the first report in 2001, there has been an increase in reported cases of dysgeusia in the form of a metallic and bitter taste disturbance, occurring directly after ingestion of pine nuts or 2−3 days later and lasting up to 2 weeks. 20 It is speculated that the consumption of seeds from Pinus armandii, considered non-edible, although added without labeling to edible species, such as Pinus koraiensis, leads to the described symptom. While efforts to identify the non-edible species through their fatty acid profile 21 or applying polymerase chain reaction (PCR) analysis 22 have been made, the mechanism of the metallic sensation is still not known.…”
Section: ■ Sources Of Metallic Sensationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first report in 2001, there has been an increase in reported cases of dysgeusia in the form of a metallic and bitter taste disturbance, occurring directly after ingestion of pine nuts or 2−3 days later and lasting up to 2 weeks. 20 It is speculated that the consumption of seeds from Pinus armandii, considered non-edible, although added without labeling to edible species, such as Pinus koraiensis, leads to the described symptom. While efforts to identify the non-edible species through their fatty acid profile 21 or applying polymerase chain reaction (PCR) analysis 22 have been made, the mechanism of the metallic sensation is still not known.…”
Section: ■ Sources Of Metallic Sensationsmentioning
confidence: 99%
“…Pine nuts, however, represent a completely different and peculiar example. Since the first report in 2001, there has been an increase in reported cases of dysgeusia in the form of a metallic and bitter taste disturbance, occurring directly after ingestion of pine nuts or 2–3 days later and lasting up to 2 weeks . It is speculated that the consumption of seeds from Pinus armandii, considered non-edible, although added without labeling to edible species, such as Pinus koraiensis, leads to the described symptom.…”
Section: Sources Of Metallic Sensationsmentioning
confidence: 99%
“…One also finds metallic characteristics reported in the assessment of various species of freshwater fish (Chambers & Robel, 1993), not to mention metallic sensations appearing in the panel rating of fresh red meat (Mitterer-Daltoe et al, 2012). Metallic is sometimes also mentioned as a sensory descriptor in the evaluation of coffee (Bicho et al, 2012), and occasionally in the dysguesia that has come to be known as pine nut syndrome (Ballin, 2012). High Unique Manuka Factor honey is occasionally described as having a metallic taste as well (cf.…”
Section: Metallic Notes Experienced In Food/drinkmentioning
confidence: 99%
“…It is intriguing to note how no matter whether it is sound, smell, or taste/flavour, metallic is often used in those situations where the sensation is unfamiliar (e.g., New York Hall of Science, 2016;Nieukirk et al, 2016) and often negatively valenced (e.g., Mesli, 2016;Pirkwieser et al, 2021). One of the other peculiar qualities of metallic taste sensations is how they tend to be long-lasting, and not necessarily obviously immediately related to what has been (or is being) consumed, be it in the case of pine nut syndrome (Ballin, 2012) or among those undergoing chemotherapy (Logan et al, 2008;see Reith & Spence, 2020, for a review). Perhaps also worth noting here is how when the stimulation associated with metallic stimuli is pleasant it is rarely described as "metallic"-consider here only the sound made by Tibetan metal singing bowls, or how sodium chloride is described as tasting salty, rather than metallic (see also Ben Abu et al, 2018), despite the latter being a metal salt (see Table 1 for a review of the taste properties associated with various metal salts/minerals).…”
Section: Metallic As a Descriptor Of Unfamiliar And Unpleasantmentioning
confidence: 99%
“…In addition, occasional cases of diarrhea, headache and nausea have been reported to be associated with this syndrome [1]. Only a few studies of PNS have been reported [3–5], and one study has described the symptoms of pine nut-related dysgeusia in a total of six subjects [6]. A single species of pine nuts ( Pinus armandii ) has previously been associated with this syndrome [1,7,8], although recent studies have reported taste disturbances from samples containing nuts from a mixture of different Pinus species [2,9,10].…”
Section: Introductionmentioning
confidence: 99%